Lepovidovstvo v romanih Gabriele Babnik Koža iz bombaža in Sušna doba - Potisk, Martina (Jezik in slovstvo, 2014)
The article examines the presence of motifs from "Lovely Vida" and the transformations of its subject matter and meaning in the novels Cotton Skin (2007) and The Dry Season (2012) by Gabriela Babnik. An overview of the findings of Ivan Grafenauer, Jože Pogačnik and Irena Avsenik Nabergoj regarding variants of the "Lovely Vida" folk ballad and the artificial reworkings of its ideational-symbolic dimensions is followed by an interpretative analysis of the aforementioned novels. The analysis demonstrates the occurrence of noticeable motif and theme variations of the third variant type of national folk ballads about Lovely Vida, which are also embedded in the contemporary context: the desire of the female characters for a better life. The Other Place with dark-skinned individuals from African countries turns into a gradual familiarisation with the Other, with which the novels serve as an illustration of intercultural oppositions.
Keywords: Slovene literature; slovenska književnost; slovenska proza; romani; Babnik, Gabriela: Koža iz bombaža; Babnik, Gabriela: Sušna doba; lepovidovstvo; lepa Vida (motiv); medkulturnost; literarne študije; interpretativne analize